The Extent of the Effectiveness of Information Technology Governance Application in Achieving the Reliability of Electronic Accounting Information Systems – A Field Study on the Commercial Bank in Tripoli City (Al-Farooq Journal of Sciences, 2026)
This study aimed to analyze the effectiveness of applying Information Technology Governance (IT Governance) in achieving the reliability of electronic accounting information systems in the commercial bank in Tripoli. The study considered the effectiveness of applying IT governance as the independent variable, while the reliability of electronic accounting information systems was the dependent variable. The study relied on a simple random sample, with the targeted sample size reaching 91 respondents. A questionnaire was used as the main tool for collecting data related to the study variables. 89 valid questionnaire forms were subjected to statistical analysis using the Statistical Package for the Social Sciences (SPSS), after excluding two forms due to incompleteness. The study followed the descriptive-analytical approach in analyzing and interpreting the relationships between its variables. It reached several results, the most prominent of which are: The results showed that the bank enjoys a good and mature level in managing the risks of electronic accounting information systems, as it has periodic practices, a clear framework, preventive procedures, and effective monitoring. The study concluded with several recommendations, the most important of which are: It is recommended to strengthen the practical aspect by conducting periodic penetration tests and expanding the scope of employee training on manipulation risks, with a focus on measuring the effectiveness of procedures quantitatively.
Keywords: Information Technology – Electronic Accounting Information Systems – Bank